Diagnostic challenges in acute monoblastic/monocytic leukemia in children - Varotto, Elena; Munaretto, Eleonora; Stefanachi, Francesca; Della Torre, Fiammetta; Buldini, Barbara (Frontiers in Pediatrics, 2022)
Acute monoblastic/monocytic leukemia (AMoL), previously defined as M5 according to FAB classification, is one of the most common subtypes of Acute Myeloid Leukemias (AML) in children, representing approximately 15-24% of all pediatric AMLs. Currently, the characterization of monocytic-lineage neoplasia at diagnosis includes cytomorphology, cytochemistry, immunophenotyping by multiparametric flow cytometry, cytogenetics, and molecular biology. Moreover, measurable residual disease (MRD) detection is critical in recognizing residual blasts refractory to chemotherapy. Nonetheless, diagnosis and MRD detection may still be challenging in pediatric AMoL since the morphological and immunophenotypic features of leukemic cells potentially overlap with those of normal mature monocytic compartment, as well as differential diagnosis can be troublesome, particularly with Juvenile Myelomonocytic Leukemia and reactive monocytosis in infants and young children. A failure or delay in diagnosis and inaccuracy in MRD assessment may worsen the AMol prognosis. Therefore, improving diagnosis and monitoring techniques is mandatory to stratify and tailor therapies to the risk profile. This Mini Review aims to provide an updated revision of the scientific evidence on pediatric AMoL diagnostic tools.